Èthos tecnologico e ricerca sociale: datiﬁcazione, computazione e sociologia digitale - Aragona, Biagio; Felaco, Cristiano (Fuori Luogo Journal of Sociology of Territory, Tourism, Technology, 2020)
The process of digitization and dataﬁcation of society have strongly impacted on the role played by technology in social research. The diffusion of new data and the development of computation for their storage,elaboration and analysis has involved an overall revision of social research tools and it has led to rethink to main issues of social science.The term "Digital Sociology” encapsulates all the innovation brought about by computation and big data and by discursive regimes that support them. Digital Sociology encourages the sociologists to pay attention to the technological èthos of social research and to deﬁne a digital method that raises, and at same time attempts to solve, old and new issues which originate in the different methodological and epistemological traditions that coexist in our discipline.